Correlated structural-optical study of single nanocrystals in a gap-bar antenna: effects of plasmonics on excitonic recombination pathways1. Issue 21 (7th June 2015) - Wang, Feng; Karan, Niladri S.; Nguyen, Hue Minh; Ghosh, Yagnaseni; Sheehan, Chris J.; Hollingsworth, Jennifer A.; Htoon, Han
<x xml:space="preserve">Abstract</x> Correlated structural-optical study of nanocrystal quantum dot/metal-antenna couples reveals that a plasmonic field does not alter Auger recombination of bi-excitons.